INTELLECTUAL POTENTIAL OF RUSSIA AS ONE OF THE KEY FACTORS IN THE MODERNIZATION - A. A. Agafonov (Модернизация, инновация, развитие, 2015)
The article describes an influence of the government support of science, education and the scientific manpower preparation system on innovation development ofRussia. It has been hypothesized that the key factor of Russian economy modernization should be the increase of financial support of research efforts and the education system.